Influence of Fertilizer Management on Sanded Soil and Its Response on Spatial Distribution of fine Roots - Souza, Huan Pablo de; Momolli, Dione Richer; Schumacher, Mauro Valdir; Ludvichak, Aline Aparecida; Malheiros, Angélica Costa; Guimarães, laudiney Couto; Gonsalves, José Mateus Wisniewski (Journal of Agricultural Studies, 2021)
The fine root component, although it represents the lowest proportional biomass in a tree, has an important function in obtaining water and nutrients. In addition, it is an indicator of the physiological quality and growth of a tree. Thus, the objective of the study was to evaluate the spatial distribution of biomass and the density of fine roots in five different fertilizer treatments. The five treatments received increasing amounts of fertilizers. The collections were made between trees in the planting line and between the planting lines. Soil layers of 25 cm x 25 cm x 20 cm (length x width x depth) were collected until reaching a depth of 1 meter. Treatments that had less nutrient input via fertilization showed higher production of fine roots. In general, the line position in the superficial layers showed a higher density of fine roots. There was significant difference between the positions of the land monoliths and between the different layers. Strategically, the lower supply of nutrients via fertilization provided greater investment in the production of fine roots by trees in order to increase the area of absorption and exploration of the soil.